Pathophysiological Evaluation of Cerecyte Coil Embolization for Experimental Broad Neck Aneurysms. (26th June 2012) - Iwamoto, Kazuhisa; Kurata, Akira; Suzuki, Sachio; Ohmomo, Taketomo; Nakayama, Shigenobu; Maruyama, Shigeyoshi; Takagi, Mamoru; Konno, Shingo; Nakahara, Kuniaki; Fujii, Kiyotaka; Yasui, Yoshie; Iwabuchi, Keiichi
Abstract : Cerecyte second-generation coils feature inner surfaces coated with an absorbable polyglycolic acid (PGA) polymer. Their use is expected to accelerate aneurysm organization, but time course data are limited. The present experimental study was therefore conducted to clarify the processes by pathological examination. Methods . Two types of experimental aneurysms were initially generated in adult mongrel dogs, one bifurcation and another of lateral wall type. Long-term persistence of each was defined by follow-up angiography for more than 1 year. Embolization of the aneurysms was then performed using only cerecyte coils, and follow-up angiography was conducted after 2 and 4 weeks followed by pathological examination. Results . Organization of both types of broad neck aneurysm was apparent 4 weeks after embolization, which is earlier as compared with already reported data for bare coils.